Kepuasan Kerja Perawat Pelaksana di Masa Pandemi COVID-19 dan Variabel yang Berhubungan - Rita Setianingrum; Rr. Tutik Sri Hariyati; Hening Pujasari; Enie Novieastari; Desnita Fitri (Journal of Telenursing (JOTING), 2021)
This study aims to identify variables that are related to job satisfaction during the COVID-19 pandemic. The research design used descriptive correlation with a cross-sectional approach. The method used is a purposive sampling technique with a sample of 185 nurses who work in the inpatient and outpatient rooms of Hospital X. Data collection uses a questionnaire in the form of google form. The results showed that there was no significant relationship between the characteristics of gender, education, marital status, work unit and career path, work experience and job satisfaction of nurses. However, the variables of age, head coaching competence and motivation have a significant relationship with nurse job satisfaction. As for the multivariate results, the constant value obtained is -0.5841, with the variables that influence coaching and motivation. In conclusion, the job satisfaction of implementing nurses during the COVID-19 pandemic is still low and the variables related to job satisfaction of nurses during the COVID-19 pandemic are coaching and motivation. Keywords: Coaching, Job Satisfaction, Motivation